Total cost of ownership of heat pumps and policy choice: The case of Great Britain - Jan Rosenow; Jacob Barnes; Ray Galvin; Samuel O'Mara; Richard Lowes (iScience)
Summary: Heat pumps are essential for decarbonizing heating, as shown by numerous studies. Their adoption depends significantly on economic attractiveness. Using Great Britain (GB) as a case study, this paper examines the total cost of ownership (TCO) for heat pumps versus gas boilers. TCO is calculated using official energy statistics, field trial data, and residential energy prices, alongside scenario analyses on business as usual, shifting levies from electricity bills to general taxation or to gas bills. Findings reveal that heat pumps provide cost savings for units performing at an above-average efficiency under standard tariffs but yield significant savings with smart tariffs. Results indicate that a carbon tax on gas, matching electricity permit prices, has limited impact. However, shifting levies from electricity to general taxation significantly enhances TCO compared to gas heating, with even greater incentives when levies are shifted to gas heating.